Words and Herbs: Julian Tuwim and the Poetry of Mindfulness - Roszak, Joanna (Czytanie Literatury. Łódzkie Studia Literaturoznawcze, 2019)
In this article, the author discusses the subject of pro-peace education with the use of poetry, and its influence on the mental well-being of children. She indicates Julian Tuwim as one of the Polish trailblazers of the 20th-century trend of mindfulness, which instructs how to establish a harmonious relationship with oneself and the environment. She discusses studies which focus on the methods used when working during school lessons of the Polish language; methods which employ mindful poetry. The author argues that there exists a relationship between internal equanimity and global peace.